1996
DOI: 10.1007/bf00242289
|View full text |Cite
|
Sign up to set email alerts
|

Continuous measurement of blood pressure, heart rate and left ventricular performance during and after isometric exercise in head-out water immersion

Abstract: Experiments were performed to determine the changes in blood pressure (BP), heart rate (HR) and left ventricular function during and after isometric knee extension during thermoneutral (35 degrees C) head-out water immersion (HWI) or in air. Seven healthy male subjects mean age 24 (SD 3) years kept their knees extended (60% maximal voluntary extension) until they reached exhaustion. The mean BP at rest was 80 (SD 10) and 78 (SD 8) mmHg [10.7 (SD 1.33) and 10.4 (SD 1.07)kPa] in air and during HWI, respectively,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…In the present study the mean peak HR (during the final 30 s of exercise in the incremental isometric exercise test) was 122.6 ± 19.0 b min -1 . This was similar to a mean peak HR of 125 b min -1 , derived from five previous double-leg isometric exercise studies (Lewis et al 1985;Misner et al 1990;Fujisawa et al 1996;Smolander et al 1998;Wiles et al 2008). The selection of 95% and 75% peak HR was based on pilot work which showed that the minimum %HR peak that could be elicited successfully, when using EMG, was 75%HR peak .…”
Section: Isometric Exercise Training Sessionsmentioning
confidence: 95%
“…In the present study the mean peak HR (during the final 30 s of exercise in the incremental isometric exercise test) was 122.6 ± 19.0 b min -1 . This was similar to a mean peak HR of 125 b min -1 , derived from five previous double-leg isometric exercise studies (Lewis et al 1985;Misner et al 1990;Fujisawa et al 1996;Smolander et al 1998;Wiles et al 2008). The selection of 95% and 75% peak HR was based on pilot work which showed that the minimum %HR peak that could be elicited successfully, when using EMG, was 75%HR peak .…”
Section: Isometric Exercise Training Sessionsmentioning
confidence: 95%
“…In both situations, decreased SVR can be explained by decreased sympathetic nervous activity, controlled by baroreflexes associated with the central shift of blood volume. 38 The hemodynamic improvement following activation of the pneumatic sleeves almost approached the baseline values recorded before inducing PPP. However, those initial parameters are probably lower than during wakefulness because of the effect of anesthesia.…”
Section: Commentmentioning
confidence: 83%
“…The increased transdiaphragmatic pressure is sufficient to draw additional blood into the thorax, thus increasing venous return. By redistributing blood from the peripheral dependent regions to the thorax, immersion causes enhanced diastolic filling of the right atrium and ventricle, evoking the Starling mechanism, thus increasing SV and CO. [35][36][37][38] In our experimental group, the abdominal cavity and lower limbs were under atmospheric pressure plus the pressure equivalent to PPP, created by the insufflated carbon dioxide and the pneumatic sleeves, and additional pressure on the legs in case of anti-Trendelenburg positioning. This counterbalanced the gravitational effects on blood distribution, thus mimicking the effect of headout immersion, in which the higher venous blood pressure in the peripheral dependent areas is counterbalanced by the higher hydrostatic pressure.…”
Section: Commentmentioning
confidence: 99%
“…Among these studies, the vast majority (76.5%) performed the handgrip, followed by knee extension (13.7%) (Table 1 , Ref. [ 8 , 13 , 18 , 19 , 20 , 22 , 23 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 ...…”
Section: Resultsmentioning
confidence: 99%